(untitled) (Lafia Journal of Scientific and Industrial Research, 2025)
This study investigates the groundwater potential of Osun State University, Osogbo campus, through an electrical resistivity survey. Using 30 Vertical Electrical Sounding (VES) points and the Schlumberger array method, geoelectric parameters such as longitudinal conductance, reflection coefficient, and overburden thickness were analyzed. The resistivity data revealed ten distinct curve types with the H curve type being the most prevalent, representing 30% of the total. The subsurface was characterized by 3 to 5 distinct layers, including topsoil, weathered layers (sandy, clayey, or lateritic), fractured basement, and fresh basement. Results showed a wide range of aquifer protective capacities. Approximately 30% of the VES points exhibited poor protective capacity, while 16.66% showed weak protection. Moderate protection was observed in 6.66% of the points, and fairly good protection in 16.67%. The remaining 13.33% had good protection, with only 3.3% rated as very good. Longitudinal unit conductance values ranged from 0.0563 to 1.1427, confirming the predominance of weak to moderate aquifer protection. Aquifers with low reflection coefficient values (r < 0.8) indicated a favourable groundwater potential but increased vulnerability to contamination. This suggests that while certain areas of the campus are vulnerable to contamination, others may offer better protection for long-term groundwater storage and use. The study underscores the importance of tailored groundwater management strategies, particularly given the rapid population growth and industrial expansion in the region, which could introduce future contamination risks. These findings are crucial for sustainable groundwater management in the campus area, ensuring protection against future contamination threats.